How Coffee Entrepreneurs in Kerinci Impact Local Economic Empowerment and Social Impact of Local Communities in terms of Financial Capital, Entrepreneurial Orientation, Government Policy and Entrepreneurial Ecosystem - Syofya, Heppi Heppi (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
In the Indonesian Kerinci region, this quantitative study explores the complex effects of coffee entrepreneurs on community well-being and local economic empowerment. This study examines the relationship between independent variables—financial capital, entrepreneurial orientation, government policy, and the entrepreneurial ecosystem—and their impact on dependent variables—entrepreneurial performance, economic empowerment, and community empowerment. It is based on the Resource-Based View (RBV) theory. A survey of 180 coffee entrepreneurs was conducted, and Structural Equation Modeling with Partial Least Squares (SEM-PLS) was used to analyze the data. The findings supported the importance of this link by showing that government policies, financial resources, entrepreneurial orientation, and the entrepreneurial ecosystem all have a beneficial impact on entrepreneurial performance, which in turn promotes community and local economic empowerment. Policy makers, coffee entrepreneurs, and industry stakeholders can benefit greatly from the findings, which highlight the significance of resource allocation, entrepreneurial qualities, and a conducive ecology in augmenting Kerinci's socio-economic advancement